TYPES OF COMPETITIVE ADVANTAGES - Terzieva, R.G (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The competitive advantage relates to the characteristics or properties of a product or brand that give the firm superiority over direct competitors. Any superiority to competitors is relative, it is determined by comparison with the best competitors on the market. The relative superiority of a competitor may be the result of various factors. In general, these factors can be divided into three categories according to the nature of the competitive advantage - a competitive advantage based on quality, a competitive advantage based on the cost of product realization and a competitive advantage based on core competences. The demand for a sustainable competitive advantage is at the heart of the strategic process and is one of the main areas of strategic marketing. The company can overtake its competitors on the market only if it manages to distinguish itself from other companies and consolidate this difference to its advantage